Cliometrics and time series econometrics: Some theory and applications - Greasley, D.; Oxley, Leslie (Wiley-Blackwell, 2010)
The paper discusses a range of modern time series methods that have become popular in the past 20 years and considers their usefulness for cliometrics research both in theory and via a range of applications. Issues such as, spurious regression, unit roots, cointegration, persistence, causality, structural time series methods, including time varying parameter models, are introduced as are the estimation and testing implications that they involve. Applications include a discussion of the timing and potential causes of the British Industrial Revolution, income 'convergence' and the long-run behaviour of English real wages 1264-1913. Finally some new and potentially useful developments are discussed including the mildly explosive processes; graphical modelling and long memory. © 2010 Blackwell Publishing Ltd.